Professional and community satisfaction with the Brazilian family health strategy - Perez,Lilian G (2013)
OBJECTIVE: To analyze the strengths and limitations of the Family Health Strategy from the perspective of health care professionals and the community. METHODS: Between June-August 2009, in the city of Vespasiano, Minas Gerais State, Southeastern Brazil, a questionnaire was used to evaluate the Family Health Strategy (ESF) with 77 healthcare professionals and 293 caregivers of children under five. Health care professional training, community access to health care, communication with patients and delivery of health education and pediatric care were the main points of interest in the evaluation. Logistic regression analysis was used to obtain odds ratios and 95% confidence intervals as well as to assess the statistical significance of the variables studied. RESULTS: The majority of health care professionals reported their program training was insufficient in quantity, content and method of delivery. Caregivers and professionals identified similar weaknesses (services not accessible to the community, lack of healthcare professionals, poor training for professionals) and strengths (community health worker-patient communications, provision of educational information, and pediatric care). Recommendations for improvement included: more doctors and specialists, more and better training, and scheduling improvements. Caregiver satisfaction with the ESF was found to be related to perceived benefits such as community health agent household visits (OR 5.8, 95%CI 2.8;12.1), good professional-patient relationships (OR 4.8, 95%CI 2.5;9.3), and family-focused health (OR 4.1, 95%CI 1.6;10.2); and perceived problems such as lack of personnel (OR 0.3, 95%CI 0.2;0.6), difficulty with access (OR 0.2, 95%CI 0.1;0.4), and poor quality of care (OR 0.3, 95%CI 0.1;0.6). Overall, 62% of caregivers reported being generally satisfied with the ESF services. CONCLUSIONS: Identifying the limitations and strengths of the Family Health Strategy from the healthcare professional and caregiver perspective may serve to advance primary community healthcare in Brazil.